Tren Wisata Sepeda Urban Masa Pandemi: Kesiapan Ruang di Perkampungan Bantaran Sungai Gajah Wong Yogyakarta - ., Wiyatiningsih; Oentoro, Kristian; Amijaya, Sita Yuliastuti (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 9 No 1 (2022): April 2022DO - 10.24843/JRS.2022.v09.i01.p04, 2022)
Cycling has become a trend during the time of the Covid-19 pandemic. The government of Yogyakarta has taken advantage of the opportunity in creating cycling tourism. It is expected that the program can reactivate tourism activities. Cycling-based tourism is organized in the administrative areas of Yogyakarta including urban kampungs. Nevertheless, it seems that not all kampungs are ready to support this strategy. Based on the background, the research aims at evaluating the spatial preparedness of kampungs on the Gajah Wong riverbank to facilitate cycling tourism. The research implements a qualitative method – an explorative case study. The kampungs on the Gajah Wong riverbank are selected due to the uniqueness of spaces and their contribution to forming the Yogyakarta image. The cycling tourism route is analyzed with five principles implemented in the Netherland - friendly infrastructure design comprising coherence, directness, safety, comfort, and attractiveness. Study results show that socio-cultural aspects play a key role in the development of spatial characteristics of kampungs located along the Gajah Wong riverbank. This becomes the primary attraction for tourists. Social interaction between tourists and residents along the kampung corridor forms a social space that has the potential to increase tourists’ experience of the Kampungs. Keywords: urban cycling tourism; kampungs; pandemic; Gajah Wong riverbank   Abstrak Bersepeda menjadi tren selama masa pandemi Covid-19. Pemerintah Kota Yogyakarta menangkap perubahan gaya hidup tersebut dengan membuat program wisata sepeda untuk membangkitkan kembali aktivitas pariwisata. Wisata sepeda dilakukan di wilayah administrasi Kota Yogyakarta, termasuk kawasan perkampungan kota. Namun demikian, sepertinya belum semua perkampungan yang dilewati oleh rute wisata sepeda siap sebagai destinasi wisata sepeda. Berdasarkan latar belakang tersebut, penelitian ini bertujuan untuk mengevaluasi kesiapan ruang di perkampungan, khususnya bantaran Sungai Gajah Wong, untuk mendukung aktivitas wisata sepeda. Penelitian ini menerapkan metode kualitatif - studi kasus eksploratif. Perkampungan di bantaran Sungai Gajah Wong dipilih sebagai studi kasus dengan mempertimbangkan keunikan ruang dan kontribusinya terhadap pembentukan karakter Kota Yogyakarta. Kesiapan ruang sebagai jalur wisata sepeda dinilai dengan lima prinsip desain infrastruktur ramah sepeda yang diterapkan di Belanda, yaitu: keterpaduan, kelangsungan, keselamatan, kenyamanan dan kemenarikan. Hasil penelitian menunjukkan bahwa aspek sosial budaya memiliki peran kunci dalam pembentukan karakteristik ruang perkampungan di bantaran Sungai Gajah Wong yang menjadi daya tarik utama bagi pesepeda. Interaksi sosial antara pesepeda dengan penduduk setempat di sepanjang lorong kampung membentuk ruang sosial yang berpotensi untuk meningkatkan kenyamanan pesepeda. Kata kunci: wisata sepeda urban; perkampungan; pandemi; bantaran Sungai Gajah Wong